Classifying Secrets in the EU1. (19th February 2014) - Galloway, David
Abstract Since 2001, the European Union has put in place a comprehensive internal and external framework for protecting classified information. This framework has brought into existence EU classified information and defines accepted common principles and standards across EU institutions, agencies and Member States for protecting it. It has been established to enable the EU to achieve its external and internal policy objectives and further its interests. This article argues that recent criticism of the EU's regulatory approach in the literature and the press is exaggerated. It explains why the EU has avoided a 'pillar'‐based legislative approach to regulating classified information based on policy domains, and forged a broad degree of convergence across EU institutions and Member States on a pragmatic approach largely based on internal rules. This has allowed the EU to emerge as a credible and capable security actor in the eyes of Member States and international partners.